Timeliness of the scientific and applied research - Zhekov, Zhivko (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The contemporary science is developing with extremely fast pace. The current material emphasizes on the timeliness of the scientific job and the scientific and applied research. Special attention is being paid of the “inner” and “outer” motivation of the scientists when choosing the problems and the approach of the methodology in the scientific research. The role of the scientific leader has been defined as a highly knowledgeable person who knows the trends in the scientific development, the market needs and who is very well prepared to look in advance into current problems and niche markets.